2013
DOI: 10.7314/apjcp.2013.14.10.5725
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cdc25c in Cell Cycle Alteration of a Radioresistant Lung Cancer Cell Line Established with Fractionated Ionizing Radiation

Abstract: Cancer patients often suffer from local tumor recurrence after radiation therapy. Cell cycling, an intricate sequence of events which guarantees high genomic fidelity, has been suggested to affect DNA damage responses and eventual radioresistant characteristics of cancer cells. Here, we established a radioresistant lung cancer cell line, A549R , by exposing the parental A549 cells to repeated γ-ray irradiation with a total dose of 60 Gy. The radiosensitivity of A549 and A549R was confirmed using colony formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
2
9
0
1
Order By: Relevance
“…In G0/G1 cells, around 80% of DSBs were repaired rapidly in the c-NHEJ pathway [42]. Similar to the results obtained by Li [43] for radioresistant A549 cells, we showed a statistically significant decrease in G1 phase and increase in the S and G2/M phases for IR-surviving H1299IR cells compared to parental H1299 cells, but not for A549IR cells. Thus, our data strongly support the notion that the presence of functional p53 resulted in durable IR-induced G1 and G2 arrests, whereas the absence of p53 led both parental and IR-surviving NSCLC cells to exiting of G0/G1 and more prominent arrest in the G2/M phase.…”
Section: Discussionsupporting
confidence: 87%
“…In G0/G1 cells, around 80% of DSBs were repaired rapidly in the c-NHEJ pathway [42]. Similar to the results obtained by Li [43] for radioresistant A549 cells, we showed a statistically significant decrease in G1 phase and increase in the S and G2/M phases for IR-surviving H1299IR cells compared to parental H1299 cells, but not for A549IR cells. Thus, our data strongly support the notion that the presence of functional p53 resulted in durable IR-induced G1 and G2 arrests, whereas the absence of p53 led both parental and IR-surviving NSCLC cells to exiting of G0/G1 and more prominent arrest in the G2/M phase.…”
Section: Discussionsupporting
confidence: 87%
“…The expression of Cdc25c was apparently higher in GSLCs than in GDCs and was almost unchanged after irradiation. Considering that Cdc25c is considered to be related to radioresistance (Zhao et al 2012;Li et al 2013), high expression of Cdc25c in GSLCs also indicates that GSLCs are more resistant to irradiation. Because the quantity of total Cdc25c protein in GSLCs is large, phosphorylated Cdc25c only accounts for a very small proportion of total protein: the remaining phosphatase Cdc25c remains sufficient to drive the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…CDC25A modulates crucial transitions between cell cycle phases during cell division, and in the case of DNA damage, it belongs to the key targets of the checkpoint machinery that ensure genetic stability [35]. Studies have shown that increased expression of CDC25A was associated with radiation resistance of tumor cells, such as advanced esophageal squamous cell carcinoma and non-small-cell lung cancer [14][15][16]. In this study, by analyzing the correlation between the expression levels of miR-122-5p and CDC25A in the cancer tissues of 77 patients with cervical cancer, we found a negative correlation between them, suggesting a potential regulatory relationship between them.…”
Section: Discussionmentioning
confidence: 99%
“…regulation of the cell cycle and induces synthesis of radiation-resistant DNA to decrease radiosensitivity of the cells [10,13]. CDC25A has been shown to induce radioresistance in a variety of tumor cells, such as non-small-cell lung cancer, esophageal cancer and colon cancer [14][15][16][17]. However, the role of CDC25A in the radioresistance of cervical cancer and its mechanism has not been fully elucidated.…”
mentioning
confidence: 99%